2019
DOI: 10.1017/s1092852919000786
|View full text |Cite
|
Sign up to set email alerts
|

Long-term functioning outcomes are predicted by cognitive symptoms in working patients with major depressive disorder treated with vortioxetine: results from the AtWoRC study

Abstract: ObjectiveAtWoRC (Assessment in Work productivity and the Relationship with Cognitive symptoms) was an interventional, open-label, Canadian study (NCT02332954) designed to assess the association between cognitive symptoms and workplace productivity in working patients with major depressive disorder (MDD) receiving vortioxetine.MethodsEligible patients with MDD received vortioxetine (10–20 mg/day) and were assessed over 52 weeks at visits emulating a real-life setting (n = 199). Partial correlation between chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 57 publications
5
48
1
3
Order By: Relevance
“…While the potential for bias cannot be excluded with self-assessment of cognitive symptoms, it is possible that subjective assessment of cognitive symptoms may more closely reflect the degree of impairment experienced by patients in daily life than objective assessment in a highly standardized test setting. 52 As in other recent studies in patients with depression, 20,23,25,26,53,54 presenteeism was found to be more prevalent than absenteeism in the study population. Patients reported missing an average of 2 working days during the previous week and over half of their time spent at work was deemed unproductive (3.7 days).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…While the potential for bias cannot be excluded with self-assessment of cognitive symptoms, it is possible that subjective assessment of cognitive symptoms may more closely reflect the degree of impairment experienced by patients in daily life than objective assessment in a highly standardized test setting. 52 As in other recent studies in patients with depression, 20,23,25,26,53,54 presenteeism was found to be more prevalent than absenteeism in the study population. Patients reported missing an average of 2 working days during the previous week and over half of their time spent at work was deemed unproductive (3.7 days).…”
Section: Discussionsupporting
confidence: 76%
“…This finding is not unexpected, as several other studies have also found discrepancies between self-reported measures and performance tests of cognitive symptoms in patients with MDD. 25,26,[48][49][50][51] For example, in a study in the United States involving 602 patients with MDD reporting cognitive symptoms, 64% met criteria for objectively defined cognitive impairment assessed using a battery of neuropsychological tests (including the DSST) and 48% met criteria for subjectively defined cognitive impairment assessed using the Cognitive and Physical Functioning Questionnaire (CPFQ). 50 Overall, 80% of patients met criteria for either subjective or objective cognitive impairment; however, only 31% met both criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of cognitive symptoms affects patient functioning broadly, including difficulty in maintaining performance at work, experiencing household and financial strains, and difficulty in participating in social life (30)(31)(32). Improvements in these symptoms have been shown to precede improvements in functional outcome, even after adjustment for depressive symptom severity (33)(34)(35). Our findings may indicate that patients experience the functional consequences of cognitive symptoms in the short term to a much greater extent than realized or observed by HCPs and therefore report them as significant over and above depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…21 The Assessment in Work productivity and the Relationship with Cognitive symptoms study (AtWoRC; NCT02332954) is an interventional, open-label, Canadian study primarily designed to assess the association between cognitive symptoms and work productivity in gainfully employed patients with MDD and who were being treated with 10-20 mg of vortioxetine daily. 22,23 The AtWoRC study was conducted in 26 centers across Canada by 9 psychiatrists and 17 primary care physicians. To be eligible, patients had to be currently experiencing a confirmed major depressive episode (MDE) for at least 3 months, and to be employed full-time (described as ≥20 h weekly) or enrolled in full-time post-secondary studies or vocational training.…”
mentioning
confidence: 99%